The Effect of Inquiry Learning Strategies and Self Regulated Learning on Critical Thinking Skills - Sholikhan, Sholikhan; Kusnadi, Kusnadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to identify students' critical thinking skills between guided inquiry and conventional learning, to determine the effect of Self Regulated Learning (SRL) on critical thinking skills, as well as to determine the effect of the interaction between guided inquiry and SRL on critical thinking skills. This study was a quasi-experimental study with a 2x2 anaphatic experimental design, which involved 128 students. The study's findings indicate that guided inquiry learning differs from conventional learning in terms of students' critical thinking skills, that SRL has an effect on critical thinking skills, and there is also an interaction effect between inquiry learning strategies and SRL on critical thinking skills.